Research on the Transparency of Civil and Commercial Arbitration from the Perspective of Generative Artificial Intelligence - Wenxi Deng (Law and Economy, 2024)
The emergence of GPT marks a significant progress in natural language processing in the field of generative artificial intelligence. Artificial intelligence has great application potential and value in legal retrieval, document review and production, arbitrator selection, and auxiliary arbitration decision-making. However, there is a contradiction between the development of artificial intelligence and the principle of arbitration confidentiality. Training a more accurate artificial intelligence model requires a large amount of diverse data, while the confidentiality of arbitration limits the acquisition and sharing of data. Therefore, in order to give full play to the potential of artificial intelligence, it is necessary to gradually increase the transparency of arbitration and achieve a balance between arbitration confidentiality and transparency through reasonable institutional design and legal norms.